Locally initiated and designed innovation and potential reverse transfer through selective bricolage at three MNC subsidiaries in China. (22nd November 2022) - Hong, Jacky F. L.; Snell, Robin Stanley
Abstract : Drawing on the concept of bricolage as 'making do' with and recombining limited resources for new purposes, our study analyzed how organization members in three MNC subsidiaries circumnavigated resource and market constraints to develop locally initiated and designed innovations in China. We developed two main contributions. First, the subsidiaries engaged selectively in bricolage, often combining it with ingénieuring, that is, formal, systematic methodologies, to bring innovations to fruition, and they could involve clients in the bricolage, through either convention‐based or familiarity‐based collaboration. The second contribution relates to reverse transfer of bricolage‐based innovations, which was especially challenging for the focal subsidiaries as they lacked global R&D mandates. Gaining HQ approval at the outset or early stages of the project, respecting the boundaries and regulations set by the HQ, establishing the pragmatic legitimacy of the solutions, and demonstrating the innovated product or service during an HQ visit appeared to be essential for reverse transfer.